2016
DOI: 10.1186/s12870-016-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis reveals alterations in development and photosynthesis-related proteins in diploid and triploid rice

Abstract: BackgroundPolyploidy has pivotal influences on rice (Oryza sativa L.) morphology and physiology, and is very important for understanding rice domestication and improving agricultural traits. Diploid (DP) and triploid (TP) rice shows differences in morphological parameters, such as plant height, leaf length, leaf width and the physiological index of chlorophyll content. However, the underlying mechanisms determining these morphological differences are remain to be defined. To better understand the proteomic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Therefore, the plant's photosynthetic efficiency and conversion capacity of photoassimilates after anthesis have become important factors for crop starch accumulation (Miralles and Slafer 2007). Polyploidization can improve photosynthetic characteristics, enzymatic activity, secondary metabolites, etc., in many plants (Meng et al 2014, Ghimire et al 2016, Liao et al 2016, Wang et al 2016. In autotetraploid plant, the basic genetic material remains the same, but gene dosage is multiplied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the plant's photosynthetic efficiency and conversion capacity of photoassimilates after anthesis have become important factors for crop starch accumulation (Miralles and Slafer 2007). Polyploidization can improve photosynthetic characteristics, enzymatic activity, secondary metabolites, etc., in many plants (Meng et al 2014, Ghimire et al 2016, Liao et al 2016, Wang et al 2016. In autotetraploid plant, the basic genetic material remains the same, but gene dosage is multiplied.…”
Section: Discussionmentioning
confidence: 99%
“…Hence autotetraploid plant has four sets of chromosomes, carries up four alleles, many genes duplicated by polyploidy retain their original function, and there is potential to enhance trait expression (Wendel 2000), e.g., improved photosynthetic characteristics have been reported in tetraploid black locust, triploid rice, etc. (Meng et al 2014, Ghimire et al 2016, Wang et al 2016, the enzyme activity of potato granule-bound starch synthase is linearly correlated with dosage of allele (Flipse et al 1996), the production of secondary metabolites displayed increased abundances in some polyploidy plants (Dhawan andLavania 1996, Lavania 2005), significant upregulation of several key enzymes related to artemisinin biosynthetic pathway was observed in autotetraploid plants of Artemisia annua (Lin et al 2011), and Ghotbi Ravandi et al (2013) reported the tetraploid plants of Cichorium intybus with a significant increase in total phenolic compounds and chlorogenic acid content in leaves. Furthermore, genes associated with photosynthesis and enzyme activities were found to be upregulated in the autotetraploid vs. diploid comparison (Fan et al 2015, Madani et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The grains were labeled at the time of owering, collected 5,6,7,8,9,10,11,12,15,18,20,21, and 24 DAF and stored at -80 °C in a freezer.…”
Section: Methodsmentioning
confidence: 99%
“…With the development of modern biotechnology, mass spectrometry (MS)-based proteomics analysis has become a powerful tool to investigate protein expression levels in a broad range of biological samples, and it has also been used to interpret the molecular details of polyploid plants, such as wheat, peanut, and black locust (Islam et al 2003; Meng et al 2016;Liu et al 2018). In terms of rice, a number of proteomic studies have focused on different organs or tissues under multiple conditions, for example, pathogen infection (Wang et al 2015), environmental challenges , and physical stress (Chen et al 2015), and proteomics and phosphoproteomics have also been applied to interpret the molecular details of early embryo development (WiĹ›niewski et al 2009;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%